2009
DOI: 10.1016/s1472-6483(10)60433-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meiotic and mitotic non-disjunction on generation of human embryonic stem cell lines

Abstract: At least 50-60% of oocytes derived from IVF procedures are chromosomally abnormal due to meiotic I or II errors. Through the use of polar body and blastomere diagnosis, euploid embryos suitable for transfer can be identified. Those embryos that are aneuploid are usually discarded, or otherwise can be used to generate chromosomally abnormal human embryonic stem cell (hESC) lines. The authors' centre has one of the largest repositories of hESC lines with genetic and chromosomal disorders generated from preimplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In a recent publication, Conlin et al [25] used a similar approach to uncover the origin of the aneuploidy in patients with chromosomal mosaicism, uniparental disomy, and chimerism. Another study aiming to derive aneuploid hESCs reported very low incidence of aneuploidies, and based on earlier biopsies of the embryos concluded that all cell lines have originated from meiotic errors [26, 27]. On the other hand, CSES16 and CSES23 carrying trisomy of chromosome 13 or X respectively, were found to originate from mitotic errors during the cleavage of the zygote.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Conlin et al [25] used a similar approach to uncover the origin of the aneuploidy in patients with chromosomal mosaicism, uniparental disomy, and chimerism. Another study aiming to derive aneuploid hESCs reported very low incidence of aneuploidies, and based on earlier biopsies of the embryos concluded that all cell lines have originated from meiotic errors [26, 27]. On the other hand, CSES16 and CSES23 carrying trisomy of chromosome 13 or X respectively, were found to originate from mitotic errors during the cleavage of the zygote.…”
Section: Discussionmentioning
confidence: 99%
“…However, human embryos are replaced whole to the uterus and do not grow in monolayer, plus they do not go through so many passages before differentiating into tissues. In addition, according to Verlinsky et al [53] abnormal embryos that self correct in monolayer had often started as normal zygotes that became abnormal postmeiotically (normal polar bodies, abnormal day 3 biopsy), and thus were already mosaics, than those that started as abnormal zygotes (abnormal polar bodies, abnormal day 3 biopsy).…”
Section: Introductionmentioning
confidence: 99%
“…Frydman et al [11] reported a low derivation rate (4.5 %) from PGDblastocysts with chromosomal abnormalities whereas Peura et al [22] and Taei et al [31] presented derivation rates of 26.8 % and 18.2 % respectively. Verlinsky et al [40,41] found a correlation between chromosomal aneuploidies and the efficiency of establishing hESC lines; they observed that embryos with aneuploidies originated from meiotic non-disjunction have a lower derivation rate than those resulting from mitotic non-disjunction. Ilic et al, [13] referred no hESC lines established from 12 karyotypically abnormal embryos versus 2 lines from 4 normal embryos.…”
Section: Discussionmentioning
confidence: 99%